How Late to Pay? Understanding Wage Arrears in Russia - John S. Earle; Klara Z. Sabirianova (W.E. Upjohn Institute for Employment Research, 2002)
We organize an empirical analysis of Russian wage arrears around hypotheses concerning factors that create incentives for firms to pay late and for workers to tolerate late payment, both reinforced by a prevalent environment of overdue wages. Our analysis draws upon nationally representative household panel data matched with employer data to show substantial interfirm variation with the probability of arrears positively related to firm age, size, state ownership, and declining performance. Estimation of a constrained multinomial logit model also reveals intrafirm variation related to job tenure and small shareholdings in the firm. Workers tend to have higher arrears in rural regions with low hiring rates, concentrated labor markets, and more prevalent arrears in the past. We argue that wage arrears, unlike wage cuts, have a theoretically ambiguous effect on workers' quit behavior, and we show empirically that the effect varies negatively with the extent of the practice in the local labor market.
Additional information: A revised version of this paper appears in the Journal of Labor Economics, Vol. 20, No. 3 (July 2002). See http://ideas.repec.org/a/ucp/jlabec/v20y2002i3p661-660.html. Please cite this revised version.
Keywords: J33; J4; J6; O12; P3; 330; Russia; pay; arrears; Earle; Sabirianova